Growing as a person: experiences at anime, comics, and games fan events in Malaysia - Yamato, Eriko (Taylor & Francis, 2016)
Gatherings organized by Japanese popular culture fans have been held since the early 2000s in Malaysia. Fan activities such as costume play (cosplay) of characters in popular culture and production of secondary products such as artwork and fanzines have captured the attention of Malaysian youth. The gatherings and conventions organized by fans are categorized as anime, comics, and games (ACG) events among the people involved. Since little attention has been given to this growing fan culture in Malaysia, a qualitative study was designed to explore ACG event participation. This article discusses aspects of autonomy, relatedness, and competence, which are considered basic psychological needs to enhance motivation for development in life. Each need is integrated and fosters the development of individuals. These three aspects were found while analyzing data from in-depth interviews of nine Malaysians who have been involved in ACG events for more than five years. The ACG events have the potential to become grounds for development when a person participates in an activity of one's own will, feels comfortable identifying with the imagined fan community which was implicit in descriptions of peers through use of the Japanese word ‘otaku’, and socializes and receives constant positive feedback through the activity.